Cognitive disability and reception of the holy Eucharist: Canons 912-913 - Burgess, Ian (CLSA advisory opinions, 2001-2005, 2001)
Our son was born with a severe case of Down Syndrome. He cannot communicate verbally. Yet as a welcome part of our family, he accompanies us to Mass. When the time comes for communion, however, the sad look on his face tells us that he would like to receive the Eucharist. What are our options as the parents of a child with special needs?